2013
DOI: 10.1371/journal.pone.0069351
|View full text |Cite
|
Sign up to set email alerts
|

MiR-146a Regulates SOD2 Expression in H2O2 Stimulated PC12 Cells

Abstract: SOD2 (superoxide dismutase 2) is one of the endogenous antioxidant enzymes that protect against reactive oxygen species. While explorations of SOD2 expression regulation are mainly focused on transcriptional and post-translational activation, there are few reports about the post-transcriptional regulation of SOD2. MicroRNAs (miRNAs) are 21nt-25nt (nucleotide) small noncoding RNAs that have emerged as indispensable regulators of gene expression. Here we show that miR-146a, a widely expressed miRNA, is up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Also, it has been shown that increased miR-146a downregulates SOD. 35 In accordance with the literature, we observed an increased miR-146a and a decreased SOD activity in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Also, it has been shown that increased miR-146a downregulates SOD. 35 In accordance with the literature, we observed an increased miR-146a and a decreased SOD activity in our study.…”
Section: Discussionsupporting
confidence: 93%
“…To investigate regulatory roles of these two miRs in periodontitis patients, we used in silico analysis (Coronnello & Benos, 2013). Indeed, in in vitro experiments (PC 12 cell line) showed that H 2 O 2 , the product of SOD activity, induced expression of miR-146a (Ji et al, 2013) which then feedback-represses SOD2 gene expression. Namely, SOD2 is an mitochondrial antioxidant enzyme but mainly, all three types of SOD act in the same manner, by catalysing neutralization of superoxide anions to oxygen and H 2 O 2 .…”
Section: Research Based On Mirs Involvement In Periodontal Disease Ismentioning
confidence: 99%
“…These data demonstrate that axonal microRNAs might play an important role in mediating the inhibitory action of CSPGs on axonal growth [67]. miR-146a, a glial-enriched microRNA [68, 69], is reported to target superoxide dismutase (SOD) 2, an endogenous mitochondrial antioxidant enzyme, and regulate cell viability in H 2 O 2 treated PC12 cells [70]. Another study shows that modulation of miR-146a expression by transfection of astrocytes with anti-miR146a or mimic regulated not only the expression levels of downstream targets of miR-146a (IRAK-1, IRAK-2, and TRAF-6), but also the expression of IL-6 and COX-2 and several cytokines such as IL-6 and TNF- α .…”
Section: Micrornas and Extrinsic Determinants Of Axon Regenerationmentioning
confidence: 99%
“…Moreover, miR-146a also directly targets some astrocyte-specific mRNAs, such as Nlgn1, Nova1, and Syt1 to induce neural stem cell to differentiate into astrocytes [68]. Interestingly, miR-146a has the opposite effect on proneuronal differentiation by targeting neuroligin 1 (Nlgn1) [70]. These data suggest that miR-146a might provide novel clues for modulating axon regeneration through targeting astrocytes.…”
Section: Micrornas and Extrinsic Determinants Of Axon Regenerationmentioning
confidence: 99%